The private world of Emily Dickinson - The Center for Humanities ([Mount Kisko, N.Y.] Makati The Center [producer] Felta Book Sales [distributor])
Presents the poetry of Emily Dickinson against the background of her new England heritage and the Atmosphere which inspired her verse in order to offer insights into the personality of the poet.
VHS
Keywords: Dickinson, Emily, 1830-1886.; Women poets, American -- 19th century